Azerbaijan and the CIS countries: societies and cultures - Ali Abasov (Scientific Research and Experimental Development, 2024)
Historically, almost everywhere cultural interaction of societies precedes (and, consequently, partly determines) it the nature of the political relations of the States representing these cultures. The history of cultural cooperation between Azerbaijan and the CIS countries is a clear demonstration of the vicissitudes of political relations between the countries divorced by the collapse of the USSR. If at the beginning of this world-historical event we witnessed the processes of chaotic rupture of ties and relations between the subjects of a once unified state, if then the newly formed states entered into serious (but not causing anything but irony after the fact) competition with each other in mastering Western values and lifestyle, then today the changed global political climate It requires a dialogue of cultures facing similar challenges and risks caused by the course and specifics of the processes of globalization and democracy/authoritarianism in the world. The presented article raises a number of issues in this regard, which are proposed for discussion.